2022
DOI: 10.1177/00187208211067575
|View full text |Cite
|
Sign up to set email alerts
|

Crew Autonomy During Simulated Medical Event Management on Long Duration Space Exploration Missions

Abstract: Objective Our primary aim was to investigate crew performance during medical emergencies with and without ground-support from a flight surgeon located at mission control. Background There are gaps in knowledge regarding the potential for unanticipated in-flight medical events to affect crew health and capacity, and potentially compromise mission success. Additionally, ground support may be impaired or periodically absent during long duration missions. Method We reviewed video recordings of 16 three-person flig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…In addition, it also implies that injuries considered as less severe on Earth (e.g., wounds, smaller burns, and bone fractures) or even smaller medical events can be inflated in severity and threaten the health of the crew, as well as impact the mission detrimentally. [21][22][23] Therefore, in situ opportunities for medical treatment could tremendously help to support these longterm human exploration missions to the Moon and eventually to Mars.…”
Section: Relevance Of Bioprinting For Applications In Spacementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it also implies that injuries considered as less severe on Earth (e.g., wounds, smaller burns, and bone fractures) or even smaller medical events can be inflated in severity and threaten the health of the crew, as well as impact the mission detrimentally. [21][22][23] Therefore, in situ opportunities for medical treatment could tremendously help to support these longterm human exploration missions to the Moon and eventually to Mars.…”
Section: Relevance Of Bioprinting For Applications In Spacementioning
confidence: 99%
“…Furthermore, these missions will be operationally and logistically very challenging, as they will endure delayed or no premature return scenarios in the case of emergencies, including those that are medically‐related, and will only allow for very limited medical capabilities in‐mission. [ 21,22 ] This differs very strongly from the current modus operandi on the ISS where medical contingencies are treated as first‐aid interventions, but surgeries would be performed on Earth (which would be reachable within less than a day). As such, future deep space missions will need a high self‐sustainability on‐board and a high autonomy of the crew of the mission.…”
Section: Relevance Of Bioprinting For Applications In Spacementioning
confidence: 99%
“…Unobtrusive measurement tools will also need to be automatically analyzed to provide timely, actionable data to the crew during communication delays with ground experts. Crews should be alerted to interventions when they are needed during critical and/or time pressured situations such as the medical situations studied by Yule et al (2022). There is much work to be done on the technology to capture the data, the software to integrate and analyze data from multiple data streams, the interface and type of data that will be provided back to the crew, and the data thresholds that will prompt an action or intervention.…”
Section: Maintaining Ground Situation Awarenessmentioning
confidence: 99%
“…Communication delays naturally increase the autonomy of the crew in space as they respond to problems in real-time. Yule and colleagues (2023) study of a simulated medical event during communication delays found that delays decrement performance and the enactment of beneficial team behaviors. When considering countermeasures for this type of situation, Mosier and Fischer (2023) examined the challenges of delays with crews in extreme analog environments.…”
Section: Planning For Behavioral Health and Performance In Complex Hi...mentioning
confidence: 99%